2015
DOI: 10.1159/000369816
|View full text |Cite
|
Sign up to set email alerts
|

Generating Conditionally Immortalised Podocyte Cell Lines from Wild-Type Mice

Abstract: Background: Understanding podocyte biology is key to deciphering the pathogenesis of numerous glomerular diseases. However, cultivation of primary podocytes results in de-differentiation with loss of specialised architecture. Human conditionally immortalised podocytes partly overcome this problem, utilising a temperature-sensitive transgene. Conditionally immortalised murine podocytes exist, but are derived from the Immortomouse. Methods: Using retroviral temperature-sensitive SV40 transfection, we created a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…Studying conditionally immortalised mouse podocytes [ 22 ], we initially demonstrated that, under basal conditions, these cells express key podocyte proteins and components of the insulin signalling cascade, which increase following podocyte differentiation (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying conditionally immortalised mouse podocytes [ 22 ], we initially demonstrated that, under basal conditions, these cells express key podocyte proteins and components of the insulin signalling cascade, which increase following podocyte differentiation (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Podocytes were isolated from perfused glomeruli from a male db/db DBA/2J and male wild-type (WT) DBA/2J littermate control mouse at 12 weeks of age. These podocytes were conditionally immortalised with temperature-sensitive SV40 transfection as previously described [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse podocytes immortalised by transduction with a temperature sensitive large T antigen SV40 construct as previously described 45 , 46 , were used as wt cells and as a background for making wt-IR, PTEN kd and PTP1B kd cell lines. The human IR sequence (NM_000208.2) in pLenti-TetCMV(IR)-Rsv(RFP-Bsd) expression vector (Gentarget) was co-transfected into Lenti-X 293 T cells (Clontech) with the packaging vectors pMD2.G (Addgene plasmid #12259) and psPAX2 (Addgene plasmid #12260) as previously reported 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown on coverslips and fixed in 4% paraformaldehyde (PFA) (Sigma), as previously described (48). Cells were blocked with 3% bovine serum albumin, and permeabilized with 0.05% Triton-X 100 (both Sigma), when needed.…”
Section: Immunofluorescencementioning
confidence: 99%